Activity of botulinum neurotoxin type D (strain 1873) in human neurons. (July 2015) - Pellett, Sabine; Tepp, William H.; Scherf, Jacob M.; Pier, Christina L.; Johnson, Eric A.
Abstract: Botulinum Neurotoxin type D (BoNT/D) causes periodic outbreaks of botulism in cattle and horses, but is rarely associated with human botulism. Previous studies have shown that humans responded poorly to peripheral injection of up to 10 U of BoNT/D. Isolated human pyramidalis muscle preparations were resistant to BoNT/D, whereas isolated human intercostal muscle preparations responded to BoNT/D similarly as to other BoNT serotypes. I n vitro data indicate that BoNT/D does not cleave human VAMP1 efficiently, and differential expression of the VAMP 1 and 2 isoforms may be responsible for the above observations. Here we examined sensitivity of cultured human neurons derived from human induced pluripotent stem cells to BoNT/D. Our data indicate that BoNT/D can enter and cleave VAMP 2 in human neurons, but at significantly lower efficiency than other BoNT serotypes. In addition, BoNT/D had a short duration of action in the cultured neurons, similar to that of BoNT/E. In vivo analyses indicated a slower time to death in mice, as well as a later onset and shorter duration of action than BoNT/A1. Finally, examination of BoNT/D activity in various rodent and human cell models resulted in dramatic differences in sensitivity, indicating a unique cell entry mechanism of BoNT/D. Highlights: The sensitivity of cultured human neurons to botulinum neurotoxin D was examined. BoNT/D enters human neurons 20–100 times less efficiently than BoNT/A. BoNT/D has a relatively short duration of action in human neurons (∼3 weeks). BoNT/D has a slower onset and shorter duration of action in mice than BoNT/A. Cultured rodent neurons have varying sensitivity to BoNT/D.